JAMUR TIRAM (Pleurotus ostreatus) UNTUK MENINGKATKAN KETAHANAN PANGAN DAN REHABILITASI LINGKUNGAN - Donowati Tjokrokusumo (Jurnal Rekayasa Lingkungan)
Oyster mushroom as a source of nutritious food and medicinal source is known since Chow Dynasti in China.However, its potential for environmental rehabilitation as known as mycorestoration is being investigatedby Paul Stamets in 2005. If oyster mushroom can control the world that could support from the smallestthings as food becoming bigger roles in the future, such as poverty eradication, improving soil fertility, andrehabilitating environmental condition, degrading toxic pollutant, protecting human health from diseases,and helping community to integrate complex waste recycle, so oyster mushroom is emerging as a strongcommodity to improve our welfare. This paper is trying to promote the role of oyster mushroom to provideits strength for both as nutrious food and medicinal source, and also for its ability to restore degraded soilfertility, and improving to remediate contaminated soils. In line with those things, and the most importantfor the people of Indonesia is trying to help increase their income through promoting mushroom cultivation,because Indonesia has a hugh potential for lignocelluslose materials and agricultural waste, and then itsspent mushroom can be used for animal feed and soil amelioration and soil remediation. Based on theStamet investigation this spent mushroom can be used for environmental rehabilitation of toxic pollutantssuch as PCB (Polychlorinated Biphenils), PAH (Polycyclic Aromatic Hydrocarbon), Azo dyes, and otherpersistent organic pollutants (POPâ€™s).Key words:Â  Oyster mushroom, Pleurotus ostreatus, mycorestoration, soil remediation, environmentalrehabilitation.